Petrogenesis and Tectonic Significance of Miocene Volcanic Rocks in the Ahlatlı-İspir-Erzurum Region, Türkiye - Erturk, Mehmet Ali; Yalcin, Cihan (Mdpi, 2025)
The & Idot;spir-Ahlatl & imath; region in northeastern T & uuml;rkiye, situated within the Eastern Pontides, hosts significant Miocene trachy-andesite volcanic rock exposures. This work seeks to elucidate their petrographic, geochemical, and isotopic compositions to enhance comprehension of their genesis and tectonic significance. Geochemistry reveals a transitional affinity, an enrichment in large-ion lithophile elements (LILEs), and a decrease in high-field-strength elements (HFSEs), suggesting a subduction-modified mantle source. Geochemical variations and fractional crystallisation trends indicate that the parental magma underwent significant differentiation, likely involving the fractionation of amphibole, clinopyroxene, and plagioclase. As supported by recent thermal modelling studies, the presence of intermediate volcanic rocks without associated bimodal suites in the study area may reflect elevated geothermal gradients and lithospheric delamination during post-collisional extension. The signatures indicated that the trachy-andesites originated in a post-collisional extensional environment after the closing of the Neo-Tethys Ocean and the ensuing tectonic reconfiguration of the Eastern Pontides. The reported geochemical traits correspond with post-collisional volcanic phases documented in various sectors of the Alpine-Himalayan orogenic system, such as the Eastern Pontides, the Iranian Plateau, and the Himalayan Belt, reinforcing the notion of a subduction-influenced mantle source. These findings increase the comprehension of magma formation in post-collisional settings and offer novel insights into the geodynamic context of the area. This research improves the understanding of post-collisional volcanic systems, their petrogenetic evolution, and their role in regional tectonic processes.
Keywords: trachy-andesite; post-collisional magmatism; Eastern Pontides; subduction-modified mantle; geochemical evolution